EFEKTIFITAS PENJATUHAN PIDANA BERSYARAT DI WILAYAH HUKUM PENGADILAN NEGERI TEMBILAHAN - Saputra, Aidil Irwan; ', Firdaus; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
It is the criminal sanctions against acts that violate the provisions of the law. In book 1 of the PENAL CODE known to the criminal sanctions contained in section 10 of the CRIMINAL CODE; principal criminal, criminal fines, imprisonment, death, confinement, caps, fines, and criminal, to repeal certain rights, deprivation of certain items, and the announcement of the verdict of the judge. Besides article 10 of the CRIMINAL CODE there is another criminal sanctions contained in other criminal sanctions contained in Article 14a-14f IE conditional criminal/criminal trial. Conditional criminal criminal system is the overthrow of a particular criminal (imprisonment, confinement, fine) where specified in the verdict that amar criminal dropped it doesn't need to be run with the imposition of certain conditions, and if the conditions specified are not followed or violated criminal then implemented. This research aims to know the effectiveness of the process of implementation of the conditional supervision of criminal verdict and what have been the barriers as well as efforts in the supervision of the overthrow of a conditional criminal jurisdiction District Court Tembilahan.This type of research can be classified in types of juridical sociological research, because in this study the authors direct research on the location or place that is examined to provide a complete and clear picture of the problems examined. This research was carried out in State Court and State Prosecutor Tembilahan. To achieve that goal the author uses field research by conducting the interview directly against the speaker on the agencies, while the population and sample is the entire parties relating to issues that are examined in this study, the digunakanyakni data sources the primary data, secondary data, and tertiary data, techniques of collecting data in this study is done with, interviews, and research libraries.The conclusions of the study results is. First, the implementation of the ruling of the Criminal Court of jurisdiction conditional Tembilahan does not run well or have not been effective. Because since 2014-2016 attorney as executors never plunge directly into the field to conduct surveillance against a convicted person conditional criminal verdict in Tembilahan District Court jurisdiction. Second, barriers experienced by the Prosecutor in conducting surveillance of criminal phenomena, among others; Yet the existence of a rule or guideline that baku against the execution of conditional criminal, administrative techniques that have not been routed from institutions with regard to the supervision of the criminal parole, lack of personnel and lack of number of working time for the Prosecutor in conducting surveillance of criminal phenomena, as well as the lack of coordination between the courts, prosecutors, police, and head of bapas. Third, When the application of the overthrow of the criminal parole implemented appropriately, then the impact it generates is as follows: Give a chance to the convicted person to improve himself in the community, enabling the convicted person to continue daily habits as a human being, in accordance with the values of the existing society, prevent the occurrence of stigma, provide an opportunity to the convicted person for participation in the works, which are economically profitable community and family.Keywords: The Effectiveness Of The Law - Conditional Criminal - Supervision